The role of motivations, emotions, strategies, and teaching in burnout experiences among Italian teachers: A cross-sectional study - Amelia RIZZO; Aanuoluwapo AFOLABI; Alessandro DE CARLO; Muhammad KAMRAN; Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: Teacher burnout is a critical issue in the educational sector, characterized by emotional exhaustion, depersonalization, and diminished professional efficacy. This study aims to investigate the interplay of motivations, emotions, strategies, and teaching in relation to teacher burnout, considering factors like job satisfaction, self-efficacy, and gender differences. Methods: A descriptive cross-sectional study was conducted among 98 Italian high school teachers in the province of Reggio Calabria. Participants, aged 38 to 64 years, completed a composite questionnaire between September and December 2023, including the Link Burnout Questionnaire (LBQ) and the Motivations, Emotions, Strategies, and Instruction (MESI) suite. Data were analyzed using IBM SPSS version 27.0. Regression analyses assessed the relationships between MESI components and burnout dimensions, with significance set at p < 0.05. Results: Higher job satisfaction was significantly associated with reduced exhaustion (estimate: -0.165; p = 0.015) and disillusionment (estimate: -0.326; p = <0.001). Emotional stressors in teaching roles predicted higher levels of burnout, while self-efficacy was linked to reduced professional ineffectiveness (estimate: -0.047; p = <0.001). Differences in satisfaction, practices, and self-efficacy were noted between high school and technical schoolteachers and between genders, with female teachers displaying higher levels of job satisfaction and self-efficacy. Discussion: The findings underscore the protective role of job satisfaction and self-efficacy in mitigating burnout among teachers. Emotional stressors related to teaching roles contribute significantly to burnout, highlighting the need for tailored interventions that support positive emotions and strengthen self-efficacy. Educational institutions should focus on developing comprehensive support systems to enhance teacher well-being and foster a positive work environment. Conclusion: Effective strategies that improve job satisfaction and self-efficacy can significantly reduce burnout among teachers. This research provides a foundation for targeted interventions to address burnout and promote resilience in educational settings.